Communicating the middle ages
1 online resource (308 pages)
Keywords: This volume is a collection of nineteen original essays by leading specialists on the history, historiography and memory of the Crusades, the social and cultural aspects of life in the Latin East, as well as the military orders and inter-religious relations in the Middle Ages. Intended to appeal to scholars and students alike, the volume honours Professor Sophia Menache of the Department of History, University of Haifa, Israel. The contributions reflect the richness of Professor Menache's research interests - medieval communications, the Church and the Papacy in the central and later Middle Ages, the Crusades and the military orders, as well as the memory and historiography of the Crusades.A Rough Guide to the Holy Land: Pilgrims' Use of the Mount Zion Library in the Fifteenth CenturyBlood-Brothers in the Thirteenth-Century Latin East? The Mamluk Sultan Baybars and the Templar Matthew SauvageEconomic, Social and Political Aspects of the Trade of the Teutonic Order in PrussiaEvidence of the Templars Religious Practice from the Records of the Templars Estates in Britain and Ireland in 1308First Officer of the Crown of France and his Legacy in the Latin East: Imbert de BeaujeuFrankish Bathhouses. Balneum and furnus A Functional dyad?Letters Home: British Crusaders in Flanders, France, Gallipoli and Palestine during World War IOn Hospitaller Initiatives in the Western Mediterranean, 1291-1307 Othon de Grandson et les Templiers dpailly Philip II and Antwerp: The Limits of RepresentationThe Templars as PeacemongersThe Genoese Expansion in the Middle Ages The Ideology of Christian Expansion in Muslim Iberia: The "Book of Deeds," Bernat Desclot and the Conquest of MajorcaThe Contested Seed of AbrahamThomas Ebendorfer and Crusading Past and PresentUrban Soundscape: Defining Space and Community in Twelfth-Century JerusalemWritten Communication in the Later Middle Ages The Letter Registers of the Teutonic Knights in Prussia.